Family, Environment, and Instagram’s Role in Juvenile Delinquency within Indorunners: Peran Keluarga, Lingkungan, dan Instagram dalam Kenakalan Remaja di Kalangan Indorunners - Kurniawan, Bima Dwi; Rochmaniah, Ainur (Universitas Muhammadiyah Sidoarjo, 2025)
In today's era, adolescent character can be influenced by factors around them such as the surrounding environment, family and social media, namely Instagram. The purpose of this study was to determine the effect of family communication, environment and Instagram media on juvenile delinquency behavior. The type of research used is quantitative. To determine the effect of family communication (X1), environment (X2), Instagram (X3) on juvenile delinquency behavior (Y). The sample used in this study was 100 adolescents. The sampling technique used simple random sampling. The results of the study indicate that hypothesis 1 is accepted, namely that there is an influence of family communication, environment and Instagram media partially and simultaneously on juvenile delinquency behavior. Based on the Adjusted R square calculation, the results obtained were 44.3% contribution from the variables of family communication (X1), environment (X2), Instagram (X3) to juvenile delinquency behavior (Y), and the correlation value between variable X and variable Y was 0.678, which means there is a strong correlation between the dependent and independent variables Highlights: Influence of Family Communication, Environment, and Instagram: These three factors affect juvenile delinquency behavior. Quantitative Study with 100 Adolescents: Using simple random sampling. 3% Contribution and Strong Correlation: These factors contribute 44.3% and have a 0.678 correlation with delinquent behavior. Keywords: Communication, Family, Environment, Instagram, Teenagers